THE HABITAT CHARACTERISTICS OF JAVAN LUTUNG (Trachypithecus auratus) IN BANDEALIT COASTAL FOREST AT MERU BETIRI NATIONAL PARK, EAST JAVA, INDONESIA - Arif Mohammad Siddiq; Hari Sulistiyowati; Nur Kholiq (BRIN Publishing (Penerbit BRIN), 2024)
Javan lutung (Trachypithecus auratus) is an endemic primate species which mostly occurs in protected areas, such as the Bandealit Resort of Meru Betiri National Park (MBNP), East Java, Indonesia. However, scientific information related to the habitat characteristics of T. auratus in this resort is limited. Therefore, the aim of this study is to investigate the habitat characteristics of T. auratus based on the vegetation stratification in the Bandealit coastal forest of MBNP. This research was conducted in March, April, May, and September 2022 using the scan sampling methods at two sites, including Site I (Camping Ground Block) and Site II (Wisma Block). The data on tree species was collected using a plot method (40 m x 20 m). Furthermore, we used the Spatially Explicit Individual-based Forest Simulator (SexI-FS) version 2.1.0 to construct the stratification profile. Based on the results, there were 17 individuals of T. auratus found in two sites along the observation. This species is recorded as occupying seven tree species, including Alstonia scholaris, A. spectabilis, Calophyllum inophyllum, Dracontomelon sp., Pongamia pinnata, Syzigium sp. and Terminalia catappa. According to stratification, T. auratus was found in Stratum B (21-30 m) to Stratum C (5-20 m) at all sites. Furthermore, this species was widely distributed in Stratum C for locomotion, foraging, social activities and self-protection. Meanwhile, T. auratus was observed using A. spectabilis in Stratum B as a sleeping tree in the afternoon and evening. These results can be the basis for in-situ conservation strategies for T. auratus species in MBNP, particularly for habitat management based on occupied vegetation.